MANAJEMEN ADMINISTRATIF PENDIDIKAN DI PONDOK PONDOK PESANTRENRAUDLATUL FIRDAUS KABUPATEN KUBU RAYA - Abdul Pandi, (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
Researchers are interested in researching this in order to find out: Administrative Management of Education at Raudlatul Firdaus Islamic Boarding School, Kubu Raya Regency. With the main problem: The concept of educational administration management at the Raudlatul Firdaus Islamic Boarding School, Kubu Raya Regency and the implementation of the educational administrative management work program at the Raudlatul Firdaus Islamic Boarding School, Kubu Raya Regency. The method used in this study is a descriptive method with a qualitative approach. The main data sources in this study were the leadership of the Raudlatul Firdaus Islamic boarding school, cleric and administrators obtained through interviews, observation, and documentation. The results of this study indicate that 1). The concept of administrative management of education at the Raudlatul Firdaus Islamic boarding school can be said to be quite good, this can be seen from every work program implementation, the Raudlatul Firdaus Islamic boarding school has implemented management functions which include: planning, organizing, mobilizing, and controlling. In every activity in Islamic boarding schools can not be separated from the concept of management that has been set by educational leaders and policies that have been formulated by the caregivers of Islamic boarding schools. 2). Then in the implementation of the administrative management functions of education at the Raudlatul Firdaus Islamic boarding school, the principle of good cooperation has been applied, this can be seen in every activity agenda for implementing the work progrem, the cooperation between the administrators is very strong, without leaving the duties of each individual. This is carried out in order that the goals of the institutional organization can be realized. After the authors conducted research and analyzed data regarding the educational administrative management work program at the Raudlatul Firdaus Islamic Boarding School, Kubu Raya Regency, it can be concluded that the Raudlatul Firdaus Islamic Boarding School has a good administrative management concept as formulated by educational experts including: planning, organizing, mobilizing, and controlling